The Low-Income Countries of the Commonwealth of Independent States : Progress and Challenges in Transition - Sattar, Sarosh (International Monetary Fund, 2004)
The CIS-7 Initiative was launched in 2002 and endorsed by ministers from the CIS-7 and donor countries, with the objective of promoting poverty reduction, economic growth, and debt sustainability among the seven poorest countries of the Commonwealth of Independent States (CIS). This volume draws from the follow-up conference held in Lucerne, Switzerland, in January 2003. The objective of this conference was to achieve an understanding of the development agenda in the seven countries and the key policy measures to be taken by the governments and donors to improve future prospects for the countries' populations.